Homework Help

What is x in 3f(x+1)-2g(x+2)=f(x)-g(x+7)?f=2x-4 g=-x+5

user profile pic

uoor | Student, College Freshman | (Level 2) eNoter

Posted January 21, 2012 at 2:21 AM via web

dislike 0 like

What is x in 3f(x+1)-2g(x+2)=f(x)-g(x+7)?

f=2x-4

g=-x+5

1 Answer | Add Yours

user profile pic

sciencesolve | Teacher | (Level 3) Educator Emeritus

Posted January 21, 2012 at 2:36 AM (Answer #1)

dislike 1 like

You need to find the equations for f(x+1),g(x+2),g(x+7).

Finding f(x+1) means to plug x+1 in equation of f(x) such that:

f(x+1)=2(x+1)-4

Expanding yields: f(x+1)=2x+2-4 => f(x+1)=2x-2

Finding g(x+2) means to plug x+2 in equation of g(x) such that:

g(x+2)=-(x+2)+5 => g(x+2)=-x-2+5 => g(x+2)=-x+3

Finding g(x+7) means to plug x+7 in equation of g(x) such that:

g(x+7)=-(x+7)+5 => g(x+7)=-x-7+5 => g(x+7)=-x-2

Plugging equations of f(x+1),g(x+2),g(x+7) in 3f(x+1)-2g(x+2)=f(x)-g(x+7) yields:

3(2x-2) - 2(-x+3) = 2x - 4 - (-x - 2)

Expanding yields:

6x - 6 + 2x - 6 = 2x - 4 + x + 2

Reducing 2x both sides yields:

6x - 12 = x - 2

You need to move the terms containing x to the left side such that:

6x - x = 12 - 2 => 5x = 10 => x = 2

Hence, the solution to the equation 3f(x+1)-2g(x+2)=f(x)-g(x+7) is x = 2.

Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes